A PERSPECTIVE STUDY IN THE ERA OF SOCIAL MEDIA BOOMING; HOW STUDENTS DISTINGUISHING FACTS AND MISINFORMATION? - Mohd Harris Bin Md Salleh; Wan Afra Binti Ibrahim (Jurnal Penyelidikan Sains Sosial, 2021)
Reading culture in many literatures has proven to be a key to success. In the new landscape of information booming catalysed by the progress of internet of things, the paradigm and mechanics of reading have also entering the new level. The purpose this study is to investigate the cultural change of reading and its patterns. Another aspect that is also taken into our focus of study is the students’ attitude on how do they accept information and distinguish between facts and misinformation. 175 respondents among semester 1 students from Politeknik Tun Syed Nasir Ismail become the subjects of this research. Mix methodology of combining quantitative and qualitative approach have been used to sought data. Data is further analysed using statistical software to come to the findings of research. Results suggest students’ behaviour and attitude and level of acceptance of information are vary among students. Significant finding between high and low achievers has shown a distinctive attitude and strategies towards distinguishing facts and misinformation.